Development Model of Local Wisdom Songket Entering The Centralized of Based on of Employee Development Market - Zaleha Trihandayani (International Journal of Management Science and Information Technology, 2023)
Opportunities for businessmen to contribute to and promote the economy can be seen in the scale of market activity in the region. In addition to the structure of the local economy, we are not supported by the strength of the structure of small and medium enterprises. The concentration of the power of small and medium-sized enterprises in the regional economic structure seems inevitable. Hollow Middle is a medium-sized and large company that cannot receive support from SMEs due to the turbulence of domestic and foreign economic conditions. A region's competitive advantage is influenced not only by its marketing advantage but also by the human resources department (HR) and operational design of regional specialty development. From this, we can conclude that: First, internal factors adversely affect employee development and have a central impact on the market. Second, centralized marketplaces have a positive impact on employee development. Third, external factors have a positive impact on employee development and concentration markets. Fourth, the internal factors of employee training and centralized markets were not important. Fifth, employee training was also not important for centralized markets. Sixth, external factors to employee development and important centralized markets.